Incomplete Markets and Fertilizer Use Evidence From Ethiopia - Larson, Donald F. (The World Bank, 2010)
While the economic returns to using chemical fertilizer in Africa can be large, application rates are low. This study explores whether this is due to missing and imperfect markets. Results based on a panel survey of Ethiopian farmers suggest that while fertilizer markets are not altogether missing in rural Ethiopia, high transport costs, unfavorable climate, price risk, and illiteracy present formidable hurdles to farmer participation. Moreover, the combination of factors that promote or impede effective fertilizer markets differs among locations, making it difficult to find a single production technology that is uniformly profitable - perhaps explaining the inconsistency between field studies finding large returns to fertilizer use in Ethiopia and survey-based studies finding fertilizer use to be uneconomic. The results suggest that households with greater stores of wealth, human capital and authority can overcome these hurdles. The finding offers some encouragement, but also implies a self-enforcing link between low agricultural productivity and poverty, since low-asset households are less able to overcome these problems. The study suggests that the provision of extension services can be effective and that lowering transport costs can raise the intensity of fertilizer use by lowering the cost of fertilizer and boosting the farmgate value of output